Managing Periorbital Necrotizing Fasciitis: How Invasive Should We Go? Poster Presentation - Case Report - Resident - Andi Marsa Nadhira; Lia Amanda; Muhammad Shafiq Advani; Lukman Edwar (Ophthalmologica Indonesiana, 2024)
Introduction : Periorbital necrotizing fasciitis (PNF) is rapidly progressive and severe infection that may result in vision loss, serious facial disfigurement, and death. Primary management includes surgical debridement; however, here we report a case in which conservative approach resulted in favorable resolution. Case Illustration : A 24-year-old male presented with swollen right upper eyelid, with watery eye, pain, and blurry vision since 1 week prior. No history of trauma or known systemic diseases was reported. Restricted movement of the right eye (RE), slight nonaxial proptosis, and skin defect along the right superior palpebra with pus, blood, necrotic and granulation tissues were found. Visual acuity (VA) of RE decreased to 6/40 with normal intraocular pressure. No abnormalities on the left eye, fever, and other signs of systemic involvement were present. Contrast orbital computed tomography (CT) scan revealed right preseptal and postseptal tissue lesions, suggesting orbital cellulitis. Initial blood work showed leukocytosis, elevated neutrophil and lymphocyte counts, and high liver function markers. The diagnosis of right orbital cellulitis with PNF was established. Skin swabs and blood cultures were taken, while intravenous ampicillin-sulbactam, bedside wound debridement, and chloramphenicol ointment application were initiated. The swab culture later showed Acinetobacter sp. The infection improved, VA was restored to 6/6, and wound closure was achieved without any surgery. Discussion : Management of necrotizing fasciitis localized in periorbita in an otherwise healthy patient may be successfully accomplished with a less invasive approach. Conclusion : Timely diagnosis and correct antibiotic therapy are mandatory to decrease morbidity and mortality related to PNF.